Stability Analysis of a Steep Rock Slope in a Large Open-Pit Mine in a High-Intensity Area: A Case Study of the Yejiagou Boron Iron Mine. (18th August 2022) - Zhang, Ying; Zhang, Jiabing; Ma, Junhua
Abstract : The slope stability of open-pit mines has always been a major problem affecting the safe production of resources from open-pit step mines. At present, slope excavation in open-pit mines is difficult and slope instability problems are becoming increasingly prominent. In this study, an open-pit bench rock slope in Liaoning Province was taken as the research object. The physical parameters of the rock mass in the area were obtained through engineering drilling and large-scale direct shear tests. Based on the determination of the dominant group of the slope's structural plane, the seepage deformation failure and maximum stress deformation of the slope were analyzed to explore the stability of high and steep rocky slopes in large open-pit mines. The results show that there is a group of dominant structural planes at the no. 1 3 observation points whose dip angle is steep and consistent with the slope inclination. The dip angle is slightly lesser at the slope toe, and the slope is basically a stable structure. The Janbu method was used to calculate the seepage stability of the slope and it is found that section 4-4 is in a dangerous area. In the stress nephogram, the maximum principal stress is located inside the slope, and the minimum principal stress is located at the surface of the free surface.